Artisanal Scale Gold Mining : A Framework for Collecting Site-Specific Sampling and Survey Data to Support Health-Impact Analyses - von Stackelberg, Katherine (Washington, DC: World Bank, 2021)
This framework document provides a pragmatic approach for designing representative studies and developing uniform sampling guidelines to support estimates of morbidity that are explicitly linked to exposure to land-based contaminants from artisanal small-scale gold mining (ASGM) activities. A primary goal is to support environmental burden-of-disease evaluations, which attempt to attribute health outcomes to specific sources of pollution. The guidelines provide recommendations on the most appropriate and cost-effective sampling and analysis methods to ensure the collection of representative population-level data, sample size recommendations for each contaminant and environmental media, biological-sampling data, household-survey data, and health-outcome data.